2017
DOI: 10.1097/cmr.0000000000000343
|View full text |Cite
|
Sign up to set email alerts
|

A multireferral centre retrospective cohort analysis on the experience in treatment of metastatic uveal melanoma and utilization of sequential liver-directed treatment and immunotherapy

Abstract: Metastatic uveal melanoma is a rare malignancy with a poor prognosis. To date, systemic therapy has been ineffective; however, there are few data on the benefits of anti-CTLA4 or anti-PD-1 antibodies in sequence with liver-directed therapy. A retrospective cohort analysis was carried out on 37 consecutive patients managed in a tertiary referral centre examining the safety and efficacy of treatment; patterns of care; and impact on survival. The sequential treatment with transarterial chemotherapy (TAC), systemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…In fact, some of our liver-directed treatments have been performed with concurrent systemic immunotherapies. Itchins et al performed a small retrospective cohort analysis of 37 patients managed in tertiary referral centers and found that transarterial chemotherapy and immunotherapy in sequence have shown to be active and reasonably well tolerated [45]. In this regard, combination treatment with immunoembolization with immune checkpoint blockades (ipilimumab and nivolumab) [NCT03472586] and radioembolization with immune checkpoint blockades [NCT02913417] are under investigation at our institution and these studies would give us more insights in the mechanism of potential survival prolongation by addition of immune checkpoint blockades to liver-directed treatments.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, some of our liver-directed treatments have been performed with concurrent systemic immunotherapies. Itchins et al performed a small retrospective cohort analysis of 37 patients managed in tertiary referral centers and found that transarterial chemotherapy and immunotherapy in sequence have shown to be active and reasonably well tolerated [45]. In this regard, combination treatment with immunoembolization with immune checkpoint blockades (ipilimumab and nivolumab) [NCT03472586] and radioembolization with immune checkpoint blockades [NCT02913417] are under investigation at our institution and these studies would give us more insights in the mechanism of potential survival prolongation by addition of immune checkpoint blockades to liver-directed treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Itchins et al [114] reported the results of a single-center cohort analysis on 37 metastatic UM patients who received a sequential therapy with transarterial chemotherapy (TAC), ICB (predominantly ipilimumab), and a systemic chemotherapy. Although the ORR was comparably poor, this combined approach led to the longest median PFS (9 months) and OS (17 months) among all therapies investigating ipilimumab.…”
Section: Ipilimumabmentioning
confidence: 99%
“…Although the ORR was comparably poor, this combined approach led to the longest median PFS (9 months) and OS (17 months) among all therapies investigating ipilimumab. However, interpreting these results may be problematic, as the authors did not distinguish between different ICB antibodies when reporting the outcomes [114].…”
Section: Ipilimumabmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies with ipilimumab, tremelimumab, nivolumab, and pembrolizumab were somewhat disappointing [77][78][79][80][81][82][83]. Slightly better results were achieved in combination therapy in which drugs against both types of ICIs receptors were used: CTLA-4 and PD-1, but still without a satisfactory breakthrough [84,85]. Another group of biomarkers targeted for cancer therapy is RTKs: IGFR, EGFR VEGFR, c-Met, and its ligands.…”
Section: Survival Timesmentioning
confidence: 99%